STRATEGIES IN DEALING WITH SPEAKING ANXIETY: A MIXED METHOD STUDY ON ENGLISH STUDENTS - Putri, Nabilah Eka; Supriusman, Supriusman; Syarfi, Muhammad (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
This study investigates strategies used by university English department students to overcome their speaking anxiety. It applied an explanatory sequential mixed method. The selected samples of the present study were 71 out of 109 population. Two main instruments used to collect the data were a questionnaire and an interview. The findings indicated that 53 students (3.74) often applied strategies to overcome their speaking anxiety. The result of the quantitative data showed that the overall mean score on the strategy applied by students to overcome speaking anxiety on positive thinking was 3.87, relaxation was 3.98, preparation was 4.05, peer seeking was 3.82, and categorized into high level respectively, while the resignation mean score was 2.99 and categorized into moderate level. Based on the interview results of 10 selected students, they applied five types of strategies above, and some students applied other strategies, such as practicing in front of the mirror and utilizing a learning tool. Since the strategies students apply have overcome their speaking anxiety, students are recommended to implement the above strategies.